Ferrochrome Slag Feasibility as a Raw Material in Refractories: Evaluation of Thermo-physical and High Temperature Mechanical Properties - Karhu, Marjaana; Talling, Bob; Piotrowska, Patrycja; Matas Adams, Alba; Sengottuvelan, Abirami; Huttunen-Saarivirta, Elina; Boccaccini, Aldo R.; Lintunen, Pertti (Waste and Biomass Valorization, 2020)
This paper reports the characteristics of ferrochrome slag and its feasibility as aggregate in refractories aiming to substitute virgin refractory raw materials. Refractory castable specimens were formulated with ferrochrome slag as an aggregate and commercial calcium aluminate cement as a binder. Objective was to prepare refractory specimens with a maximum slag utilization but simultaneously to sustain good properties, comparable to those of virgin raw material refractory products. Mechanical and thermo-physical properties of the cured, dried and sintered specimens were characterized. Cold crushing strengths of best performing ferrochrome slag containing specimens were higher than 90 MPa and compressive strength values measured at 1200 °C were over 9 MPa. Thermal insulation properties were even better than those of commercial refractory reference, showing thermal conductivity values as low as λRT−1000 °C = 1.3 − 0.9 W/m K. The liquid phase formation above 1200 °C limits the ferrochrome slag use for refractory applications. Results suggest ferrochrome slag’s feasibility as an aggregate raw material for refractory materials up to temperatures of 1200 °C in air and up to temperatures of 700 °C in acidic gaseous atmosphere. Possible applications for this kind of novel refractory materials are, e.g., insulating secondary layers or bottom zones in metallurgical processes to substitute virgin refractories. A direct contact to molten metal must be avoided, but they are applicable as, e.g. floorings when exposed only to occasional melt droplets. Graphic Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2020-06-02
Keywords: Electric arc furnace slag; Ferrochrome slag; Refractory ceramics; Slag valorisation